Abrasive based finishing method applied on biomedical implants: A review. (2021) - Kumar, Manjesh; Kumar, Abhinav; Yadav, H.N.S; Alok, Anupam; Das, Manas
Abstract: Surface quality is a key parameter affecting product life and functionality. Most of the technologies have been produced in the past that can be used for a micrometre or submicrometre accuracy, nanometer surface roughness and almost no surface defects in the production of optical, mechanical and electronic products. Such technologies for finishing have been divided into two types: including and not including magnetic field support. These processes having flexible finishing tool that can be employed for complex freeform components effectively. In the case of finishing complex freeform surfaces, traditional finishing methods are comparatively inferior in performance due to the lack of controlling finishing forces and limitations of polishing tool movement over the components' complex freeform contour. Surface conditions of biomedical components (knee joint, hip joint, elbow joint, heart valve, dental crown etc.) decide the life and functionality of the implant. Generally, implants are made from skin, bone or other body tissues and also metals, plastics, ceramics or other materials. Abrasive finishing is a non-traditional finishing technique that offers better finishing accuracy, performance, consistency and economy. This article discusses the published works on fine finishing of biomedical implants to improve their functionality and surface quality through abrasive based finishing methods, including abrasive flow machining, magnetorheological fluid-based finishing, magnetic abrasive finishing, etc.